Palaeoenvironmental and palaeoceanographic changes during the lower to middle Jurassic (Toarcian-Aalenian, ~183-171 Ma). : new evidences from calcareous nannofossils of the Lusitanian Basin - Ferreira, Jorge Humberto Gomes, 1972- (2016)
Tese de doutoramento (co-tutela), Geologia (Paleontologia e Estratigrafia), Faculdade de Ciências da Universidade de Lisboa, Université Claude Bernard Lyon 1, 2016